Performance of Microencapsulated Fungicide in Exterior Latex Paint on Wood Substrate - Ibrahim, Wan Asma; Mat Seman, Ahmad Shakri; Mohd Nasir, Nurul Huda; Sudin, Rahim (1989)
3-iodo-2-propynyl butyl carbamate (IPBC) was encapsulated by in situ polymerization of urea formaldehyde resin of crosslink (formaldehyde: urea) ratios 1 and 2. The leaching rate of the microcapsules was reduced compared to the free fungicide. Microcapsules prepared at the higher urea formaldehyde cross ink ratio gave a lower leaching rate. Two concentrations based on the weight of the active ingredient per volume of paint (a.i.lv) of 0.3 % and 1 % of microcapsules or free IPBC were incorporated into exterior latex paint and applied onto rubber wood panels. The panels were then exposed to the environment. A longer protection from discoloration was provided by the encapsulated IPBC of 1% concentration.